ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN DAERAH PEMERINTAH PROVINSI MALUKU - Tuasikal, Mundawansa; Latuamury, Jabida (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
This study aims to assess the financial performance of the Provincial Government of Maluku by analyzing key financial ratios from 2019 to 2023, including regional financial independence, revenue effectiveness, budget efficiency, expenditure harmony, and fiscal growth. As a province characterized by insular geography and high dependence on central government transfers, Maluku presents unique fiscal challenges. The study employs a descriptive quantitative approach using annual data from the Regional Budget Realization Reports. The novelty of this research lies in its comprehensive evaluation of fiscal dynamics in a remote island region, contrasting with prior studies that mainly focus on mainland areas. The results indicate that the financial independence ratio consistently falls into the